Analyzing Subulussalam Community's Views on Electoral Money Politics in 2024: Implications for Leadership and Its Benefits - Syafrowi, Syafrowi; Tanjung, Dhiauddin; Siregar, Ramadhan Syahmedi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to explore the perception of the citizens of Subulussalam towards the phenomenon of political bribe in the 2024 legislative election (PEMILU) and analyze its impact on the leadership and benefits of the community in Subulussalam City. The political bribe that occurs is often considered commonplace and culturalizes people's habits that are aware or do not damage democracy through the quality of community representation through the legislature. This research uses a qualitative approach with a case study method, involving in-depth interviews with various key informants, including voters, politicians, and academics in Subulussalam. The results of the study show that there are various election violations, especially violations in terms of political bribery to get votes. When viewed from the perspective of Islamic law, money politics is seen as an illegal act because it violates the principles of justice and trust as stated in Maqashid Sharia. Meanwhile, from a formal legal perspective, this practice is considered a criminal act that must be eradicated to maintain the integrity and credibility of the election process. In terms of social impact, money politics in Subulussalam City in the election of legislative members has had an impact on the level of public trust in the political system and government which is greeted by rampant collusion and nepotism in the election. This study concludes that to realize quality leadership and benefit the people of Subulussalam, there need to be serious efforts from various parties to eradicate money politics by establishing an election system that is not tied to the party. Candidates are also expected to provide transparent information regarding campaign funding, funding sources, and financial coverage. This is useful for limiting the practice of unnatural distribution of money and capital among candidates and parties. Political education, strict law enforcement, and increasing public awareness of the importance of voting based on the competence and integrity of prospective leaders are also needed to achieve these goals.